Process Mapping in a Pediatric Emergency Department to Minimize Missed Urinary Tract Infections - Morgan Black; Valene Singh; Vladimir Belostotsky; Madan Roy; Deborah Yamamura; Kathryn Gambarotto; Keith Lau; April J. Kam (Hindawi Limited, 2016)
Urinary tract infections (UTIs) are common in young children and are seen in emergency departments (EDs) frequently. Left untreated, UTIs can lead to more severe conditions. Our goal was to undertake a quality improvement (QI) initiative to help minimize the number of children with missed UTIs in a newly established tertiary care pediatric emergency department (PED). A retrospective chart review was undertaken to identify missed UTIs in children < 3 years old who presented to a children's hospital's ED with positive urine cultures. It was found that there was no treatment or follow-up in 12% of positive urine cultures, indicating a missed or possible missed UTI in a significant number of children. Key stakeholders were then gathered and process mapping (PM) was completed, where gaps and barriers were identified and interventions were subsequently implemented. A follow-up chart review was completed to assess the impact of PM in reducing the number of missed UTIs. Following PM and its implementation within the ED, there was no treatment or follow-up in only 1% of cases. Based on our results, the number of potentially missed UTIs in the ED decreased dramatically, indicating that PM can be a successful QI tool in an acute care pediatric setting.